The Role of Academic Supervisor in Students of Physical Education and Sport Sciences Field Performance Training in Schools - Khadair, Yasir; hamdan, Abdullah Ghazi (Journal of Physical Education, 2023)
The research aimed at designing two scales for academic supervisor role and the effect of field training for students. In addition to that, the research aimed at identifying the relation between academic supervisor role and fourth year college of physical education and sport sciences students /university of Baghdad. The researchers used the descriptive method to design two scales one for academic supervisors and another for field application. Each scale consisted of (15) items applied on (176) teachers and (362) forth year female and male students. Field application lasted for (6) months, the subjects were (74) teacher, and (154) female and male students. The results showed that both scales have a strong correlation.